Systems thinking and modelling to support transformative change: key lessons from inter-disciplinary analysis of socio-ecological systems in applied land systems research - Miriam Glendell; Matt Hare; Kerry A. Waylen; Kerr Adams; Jean Léon Boucher; Zisis Gagkas; Alessandro Gimona; Simone Martino; Keith B. Matthews; J. Gareth Polhill (Discover Sustainability)
Abstract The evolving ‘permacrisis’ of compounding environmental and social challenges calls for transformative approaches to understanding and intervening in socio-ecological systems. Approaches to support systems thinking and understanding can be vital to achieving this goal. However, applying such systems thinking is often challenging, and we need to better reflect on the pros and cons of different approaches for building systems understanding and informing changes. In this paper, we first identify key attributes of systems thinking approaches from literature. We then use these as a framework for comparing and evaluating seven different systems thinking approaches, selected on the basis of our experience in applying them in support of the management and governance of various types of land systems. The seven approaches are: agent-based modelling, Bayesian belief networks, causal loop modelling, spatial multicriteria analysis, societal metabolic analyses, social network mapping and quantitative story telling. This framework has allowed us to appraise and reflect on our own experiences to identify the respective strengths and weaknesses of these different methodologies. We note that some of the ability to inform change depends as much on the context within which specific tools are used as the particular features of the tools themselves. Based on our appraisal, we conclude by suggesting six key recommendations that should be followed by others seeking to commission and use systems approaches, in order to enable them to support transformative change. We hope this may be useful to those working with systems approaches, since there is an urgent need for analytic efforts that can inform and enable transformative change. We also reiterate the call for sustained funding for long-term, standards-based evaluation of systems thinking approaches with respect to whether their use can demonstrate instrumental impacts leading to the kind of transformation the IPCC has called for, i.e. fundamental system change that goes beyond capacity development impacts such as network-building.